The importance of free stretches in a dammed river to the maintenance of Schizodon intermedius populations - Nobile, André Batista [UNESP]; de Lima, Felipe Pontieri [UNESP]; Freitas-Souza, Diogo [UNESP]; Paes, Jaciara Vanessa Kruger [UNESP]; Britto, Sandro Geraldo de Castro [UNESP]; Vidotto-Magnoni, Ana Paula (Boletim do Instituto de Pesca, 2019)
This paper focuses on to evaluate the importance of a free stretches upstream of a Neotropical reservoir for the maintenance of Schizodon intermedius populations, a medium size migratory species and important fisheries resources. Quarterly samplings were carried out in 8 sampling sites, distributed in Jurumirim Reservoir and two tributaries upstream reservoir. Reproductive, populational and feeding strategies were used to evaluate the importance of each sample area in the biological cycle of this species. Results showed that S. intermedius makes different uses of the sites. In the rainy season, individuals in the lower areas presented higher condition factor and average repletion degree of stomach, assuming that are used for growth and feeding and; in the upper areas, higher size and GSi values, suggesting that are reproductive area. We conclude that Schizodon intermedius uses lentic areas to gain energy in dry season, and in the rainy season, uses this energy to migrate to lotic stretches to reproduction. The stretches upstream free of dam are essential for this migratory species maintain viable populations in an environment impaired by dams.
A importância de trechos livres de barramento em ambientes represados na manutenção de populações de Schizodon intermedius
Keywords: Damming impacts; Fish migration; Fisheries ecology; Fisheries resources; Neotropical ichthyofauna